The Late Ordovician and Early Silurian pentameride brachiopod Holorhynchus Kiaer, 1902 from North China - Rong, JY (戎嘉余); Zhan, RB (詹仁斌); Jin, JS (PALEONTOLOGICAL SOC INC, 2004)
Holorhynchus giganteus Kiaer, 1902, a common Late Ordovician (mid-Ashgill) pentameride brachiopod in the Baltic region, Kazakhstan, and southern Tien Shan, is documented for the first time from the Badanjilin Formation (mid-Ashgill) of western Inner Mongolia (Alxa block), North China. Serial sections of the Chinese material confirm the presence of a vestigial ventral median septum in the early growth stage of H. giganteus, but the septum becomes embedded in the secondary shell thickening at the adult growth stage. A survey of the type material from Norway and additional material from other regions indicates that the incipient ventral median septum is a much more commonly developed structure than was previously believed. The presence of a well-developed pseudodeltidium in the Tien Shan material of H. giganteus and the absence of such a structure in conspecific material from many other regions require a systematic revision of the generic group. Holorhynchus has rodlike crura (=brachial processes) that do not form flanges at their junctions with the inner hinge plates (=outer plates crural plates) and outer hinge plates (inner plates). This, together with the development of a crude spondylial comb structure, points to its affinity to the Virgianidae rather than to the Stricklandiidae. Holorhynchus can be regarded as a Lazarus taxon because of its absence during the crisis (Hirnantian) and survival (early-middle Rhuddanian) intervals associated with the Late Ordovician mass extinction and its reappearance in Kazakhstan and North China during the Early Silurian (late Rhuddanian-early Aeronian), The mid-Ashgill Holorhynchus fauna, typified by a number of large-shelled pentamerides, was common in the Baltic region, the Urals, Kazakhstan, Tien Shan, AIxa, Qaidam, Kolyma, and east-central Alaska, but largely absent from Laurentia and Siberia (except for Taimyr) in the ancient tropical-subtropical regions. This paleobiogeographic pattern agrees with the general pattern of the Late Ordovician brachiopod provincialism.